Dose-mortality, Cytotoxicity and Repellent Activity of Abutilon hirtum (Lam.) Sweet against Callosobruchus chinensis (L.), Artemia salina L. and Tribolium castaneum (Hbst.) (Journal of Scientific Research, 2017)
Petroleum ether (Pet. ether), chloroform (CHCl3) and methanol (CH3OH) extracts of the aerial parts of Abutilon hirtum (Lam.) Sweet were subjected to dose-mortality against the stored grain pest Callosobruchus chinensis (L.), cytotoxicity against brine Shrimp Artemia salina L. nauplii and repellent activity against adult beetles of Tribolium castaneum (Hbst.). Against C. chinensis only CH3OH extract showed promising mortality and provided LD50 values 1.344, 1.294, 1.243 and 1.152 mg/cm2 after 6, 12, 18 and 24 h of exposure respectively, however, Pet. ether and CHCl3 extracts didnt show mortality. Against A. salina nauplii Pet. ether, CHCl3 and CH3OH extracts showed cytotoxic effects; while Pet. ether extract gave LC50 values 2461.031, 642, 191.233, 94.618 ppm after 6, 12, 18 and 24 h of exposure respectively, and CHCl3 extract provided LC50 values 1336.124, 679.387, 276.961 and 199.988 ppm; and CH3OH offered 531.896, 212.840, 91.499 and 72.975 ppm after 6, 12, 18 and 24 h of exposure respectively. For repellency against T. castaneum adults CHCl3 extract showed significant result at 1% level of significance (P < 0.01), while the CH3OH extract showed moderate repellency at 5% level of significance (P < 0.05), but the Pet. ether extract didnt show any significant repellent activity.